The use of "Pruteen1" in broiler diets - Mak, T. K.; Oh, B. T. (Universiti Pertanian Malaysia, 1983)
A study, involving 1,200 birds., was conducted to compare the performance of birds fed pruteenbased and commercial diets. The mean individual feed intake, weight gain and feed conversion ratio (F.eR.) of birds fed the pruteen-based diet were 4673.8 g, 2172.3 g and 2.15 respectively, whereas in those fed the commercial diet they were 4832.5 g, 2151.8 g and 2.25 respectively. Birds fed the pruteen-based diet consumed significantly less feed and had better F. C.R. (P < 0.05). However the difference of 20.5 g in weight gain/bird in favour of the pruteen-based diet was not found to be significant. Mortality figures of 4.5% and 3.8% respectively of birds fed pruteen-based and commercial diets were considered normal. There was a difference of $0. 0878 in the feed cost/bird in favour of the pruteen-based diet.